Effects of green tea and green coffee extracts, empaglyphozin, and metformin on CAMLG mRNA expression in aortic calcification in Sprague Dawley rats induced by an atherogenic diet - Riswati, Harnanik Puji; Rohman, Mohammad Saifur; Cholid Tri Tjahjono (Heart Science Journal, 2026)
Background: Metabolic syndrome (MetS) in rat models, typically induced by high-fat or high-fructose diets, mirrors human features such as central obesity, insulin resistance, dyslipidemia, and hypertension. These metabolic disturbances create a pro-inflammatory, oxidative environment that actively drives vascular calcification through osteogenic transformation of vascular smooth muscle cells (VSMCs). Diet-induced obesity models have shown that high-fat diets can trigger and accelerate aortic calcification in vivo. Objective: This study aimed to determine whether MetS promotes vascular calcification and alters aortic CAMLG mRNA expression in rats, and to evaluate the effects of green tea/coffee extract, metformin, and empagliflozin on CAMLG modulation. Methods: Twenty-five male Sprague-Dawley rats were divided into five groups: negative control, MetS (high-fat/high-sucrose diet plus streptozotocin), and three treatment groups (green tea/coffee extract, metformin 500 mg/kg, empagliflozin 30 mg/kg). After nine weeks, aortic calcification was assessed via hematoxylin-eosin staining, and CAMLG mRNA expression was quantified by qRT-PCR. Data were analyzed with Kruskal-Wallis and post-hoc tests. Result: MetS induction promoted vascular calcification. CAMLG mRNA expression was higher in the MetS group compared to controls, though not statistically significant. All treatments modestly reduced CAMLG levels, but differences were not significant (p = 0.051), possibly due to multifactorial influences. Conclusion: MetS may tend to vascular tissues for calcification altering CAMLG mRNA expression. Therapies targeting oxidative stress, inflammation, or glucose metabolism could potentially modulate CAMLG-related pathways, warranting further exploration of underlying mechanisms.